Perancangan Sistem Komunikasi Kabel Laut (SKKL) Fiber Optik Link Surabaya-Bawean - Endang Retno Nugroho; Rianto Nugroho (Jurnal Ilmiah Giga, 2022)
Abstract. Internet network is an important requirement in the digital era. Indonesia is listed as the country with the highest data traffic growth in the world in 2016. To meet the needs of this data traffic, network access is needed. Indonesia has a geography that mostly covers the ocean. The islands lined up from Sabang to Merauke up to tens of thousands. This large number of islands is a problem in building communication infrastructure. Bawean Island is one of the islands in Indonesia with an area of 197 km2 with a population of more than 100,000 people in 2021. The pre-existing communication access is communication with VSAT using Satellite and Radio Wave Communication. Both types of communication have limitations in bandwidth capacity. In this research, it is proposed to design a Marine Cable Communication System (SKKL) for data access on Bawean Island. Data traffic is sent via optical fibre from the city of Surabaya to the island of Bawean which is 235 km away. In this design, we use a single-mode G.655 cable type and 5 optical amplifiers of the EDFA type. The results of the design show that the power link budget is -9.525 dBm, SNR 25.35 dB, Q-factor 9.26, and BER 1.009×10^-20. Abstrak. Jaringan internet merupakan suatu kebutuhan penting di era digital. Indonesia tercatat sebagai negara dengan pertumbuhan trafik data tertinggi di dunia pada 2016. Untuk pemenuhan kebutuhan trafik data ini dibutuhkan akses jaringan. Indonesia memiliki geografis yang sebagian besar meliputi lautan. Pulau-pulau berjajar dari Sabang sampai Merauke jumlahnya hingga puluhan ribu. Jumlah pulau yang banyak inilah yang menjadi permasalahan dalam membangun infrastruktur komunikasi. Pulau Bawean adalah salah satu pulau di Indonesia dengan luas 197 km2 dengan penduduk lebih dari 100.000 jiwa pada tahun 2021. Akses komunikasi yang sudah ada sebelumnya adalah komunikasi dengan VSAT yang memanfaatkan Satelit dan Komunikasi Gelombang Radio. Kedua jenis komunikasi ini memiliki keterbatasan dalam kapasitas bandwidth. Dalam penelitian ini diusulkan perancangan Sistem Komunikasi Kabel Laut (SKKL) untuk akses data pulau Bawean. Trafik data dikirimkan melalui serat optik dari kota Surabaya menuju pulau Bawean yang berjarak 235 km. Dalam perancangan ini menggunakan tipe kabel singlemode G.655 dan 5 buah optikal amplifier jenis EDFA. Hasil perancangan menunjukan besarnya power link budget -9.525 dBm, SNR 25.35 dB, Q-factor 9.26, dan BER 1,009×10^-20.